2012
DOI: 10.1007/s00441-012-1415-7
|View full text |Cite
|
Sign up to set email alerts
|

Src-signaling interference impairs the dissemination of blood-borne tumor cells

Abstract: Although solid tumors continuously shed cells, only a very small fraction of the neoplastic cells that enter the blood stream are capable of establishing metastases. In order to be successful these cells must attach, extravasate, proliferate, and induce angiogenesis. Preclinical studies have shown that small-molecule ATP-competitive Src kinase inhibitors can effectively impair metastasis associated tumor cell functions in vitro. However, the impact of these agents on the metastatic cascade in vivo is less well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…Two key signaling controllers, the non-receptor tyrosine kinase c-Src, and the receptor tyrosine kinase c-Met, have been strongly implicated in metastasis (Trusolino et al, 2010; Dai et al, 2012; Siemann et al, 2012). Functionally, these critical signaling molecules modulate multiple cell functions including migration, invasion, survival, and angiogenesis.…”
Section: 0 the Impact Of The Tumor Microenvironment On Cancer Treatmentioning
confidence: 99%
See 1 more Smart Citation
“…Two key signaling controllers, the non-receptor tyrosine kinase c-Src, and the receptor tyrosine kinase c-Met, have been strongly implicated in metastasis (Trusolino et al, 2010; Dai et al, 2012; Siemann et al, 2012). Functionally, these critical signaling molecules modulate multiple cell functions including migration, invasion, survival, and angiogenesis.…”
Section: 0 the Impact Of The Tumor Microenvironment On Cancer Treatmentioning
confidence: 99%
“…With regard to the former, trastuzumab, a monoclonal antibody that interferes with the HER2/neu receptor, also has been reported to inhibit VEGF expression (Petit et al, 1997). Similarly, the small molecule Src targeting agents saracatanib and dasatinib significantly reduce tumor angiogenesis both in vitro and in vivo (Siemann et al, 2012; Rice et al, 2012). Interestingly, protolytic enzymes long recognized as major contributors to the dissemination of tumor cells not only can elicit pro-angiogenic endothelial cell function but their selective targeting can impair tumor associated angiogenesis (Sudhan et al, 2015).…”
Section: 0 the Tumor Microenvironment As A Double Edged Swordmentioning
confidence: 99%
“…Previous studies in our lab have demonstrated that hypoxia and HIF-1a are strongly associated with invasiveness and disease progression in prostate cancer 31–33. Interestingly, although we have shown the critical role of several oncogenic TKs including Src in prostate cancer cell migration and invasion,23,34 whether Src or other non-Src SFKs could be regulated under oxygen-depleted environments remained largely unknown. The current study reports that c-Src, the major SFK member, is significantly upregulated by hypoxia that triggers elevated functions, indicating the potential role of c-Src in prostate cancer metastasis, but not cell proliferation, particularly under adverse tumor microenvironments.…”
Section: Discussionmentioning
confidence: 67%
“…As such, inhibiting SFKs may have therapeutic benefit for cancer patients [ 2 , 3 ]. Phenotypic aberrations in the cellular processes mentioned above are often associated as well with non-canonical TGF-β signaling [ 4 6 ]. Indeed, as reported for SFK inhibitors, TGF-β inhibitors can reduce bone metastasis of breast cancer and melanoma [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, in primary leukemic lymphocytes dasatinib resistance was shown to be associated with differential dependency on autophagy, mTORC1 and AMPK signaling for survival [ 14 ]. The involvement of AMPK, ER-stress and autophagy in dasatinib resistance have been recently reported as well in prostate cancer cells [ 5 , 6 ]. AMPK is a sensor of bioenergetic stress activated by LKB.…”
Section: Introductionmentioning
confidence: 99%